Brand Equity as Mediator in the Effect of Viral Marketing and Online Reviews on Impulsive Buying of Fashion Product - Azizah, Nurifa Laksmitasari; Pratiwi, Hasna Widya; Apriliyanto, Nanang (Jurnal Manajemen, 2026)
This study aims to analyze potential strategic factors that marketers can leverage, particularly considering the impulsive nature of Indonesian consumers when purchasing fashion products. This study offers novelty by integrating viral marketing, online customer reviews, brand equity, and impulse buying into a single empirical framework within the context of the Indonesian fashion industry. It also provides context-specific insights for online fashion businesses in emerging markets, contributing both theoretically and practically to digital consumer behavior research. This research is categorized as an explanatory study based on a causal approach. The population consists of individuals who frequently purchase fashion products through e-commerce platforms, specifically, those who have made more than one purchase per month over the past three months. A total of 150 respondents were selected as the sample for this study. This research is a primary data type research using a questionnaire via Google Form. Data were processed using Smart PLS (Partial Least Squares), a statistical analysis tool suitable for examining complex variable relationships. This study contributes scientifically by integrating viral marketing, online customer reviews, and brand equity into a single framework that explains impulse buying behavior in the digital fashion industry. It provides empirical evidence that brand equity acts as a key mediating factor, strengthening the indirect influence of digital marketing strategies on consumers' impulse buying decisions.